2022
DOI: 10.3390/coatings12050577
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Biodegradable Food Packaging and Edible Coating Materials in the COVID-19 Era: A Mini-Review

Abstract: With the onset of the COVID-19 pandemic in late 2019, and the catastrophe faced by the world in 2020, the food industry was one of the most affected industries. On the one hand, the pandemic-induced fear and lockdown in several countries increased the online delivery of food products, resulting in a drastic increase in single-use plastic packaging waste. On the other hand, several reports revealed the spread of the viral infection through food products and packaging. This significantly affected consumer behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…CoV virion is classified as a very pathogenic virus [94]. SARS-CoV-2 is the third virus in the coronavirus family that has globally caused serious ailments in humans [95]. The virus particles are transmitted through human-to-human contact or contact with infected individuals mediated through the eyes, mouth, nose, or through the inhalation of exhaled virus in respiratory droplets [94].…”
Section: The Antiviral Properties Of Active Food Packagingmentioning
confidence: 99%
See 2 more Smart Citations
“…CoV virion is classified as a very pathogenic virus [94]. SARS-CoV-2 is the third virus in the coronavirus family that has globally caused serious ailments in humans [95]. The virus particles are transmitted through human-to-human contact or contact with infected individuals mediated through the eyes, mouth, nose, or through the inhalation of exhaled virus in respiratory droplets [94].…”
Section: The Antiviral Properties Of Active Food Packagingmentioning
confidence: 99%
“…However, adding antiviral materials as a layer containing antiviral agents to a coating carrier or incorporating them into a matrix of active films is a strategic route to develop antiviral packaging systems. Multilayered packaging systems are being developed through coextrusion, lamination, or covering with coatings [95]. This safe packaging should have an internal coating or extruded film layer to protect food products and an external coating or extruded film layer with antiviral compounds to protect customers (Figure 2) [94][95][96][97][98].…”
Section: The Antiviral Properties Of Active Food Packagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The long stability of SARS-CoV-2 on the surfaces of packaging materials created substantial risks during handling production until consumption. Cross-contamination hazards from infected food handlers are also one of the major routes of transmission of the virus via food [ 129 ]. Recent research has confirmed that coronavirus remains infectious on surfaces including glass (5 days), cardboard (8 h), silicon (5 days), PVC and Teflon (5 days), plastic (polypropylene) (2–3 days) and other plastics (72 h to 6 days) at room temperature [ 130 , 131 ].…”
Section: Antiviral Food Packagingmentioning
confidence: 99%
“…Several biopolymers, such as proteins, polysaccharides, lipids, and their mixtures, have been investigated in this regard [ 1 ]. In addition to being environmentally friendly, biopolymers have enormous promise for delivering functional ingredients and regulating their release, opening the door to the fabrication of active packaging [ 2 ]. Additionally, biopolymers are crucial for various advanced applications such as biomedical engineering due to their controlled-release property, non-toxicity, hydrophilicity, biocompatibility, and biodegradability [ 3 ].…”
Section: Introductionmentioning
confidence: 99%